Atypical disfluency: understanding and treating word-final (end-word) repetition - Sisskin, Vivian (Henry Stewart Talks, 2017)
Atypical speech disfluency (word-final repetition) in comparison to stuttering, Multi-dimensional profiles of word-final disfluency in children with & without autism, Considerations for treatment planning, Short-term behavioral treatment, Case studies in neurotypical children and children with autism